Field test and load spectrum compilation on the drive shaft of feeding and conveying device for combine harvesters - Zhang, Fu; Li, Xiaoshuai; Huang, Shengcao; Guo, Zhiqiang; Yu, Zhiwei; He, Huawei; Wang, Pengfei (International Journal of Agricultural and Biological Engineering, 2026)
The feeding and conveying device for combine harvester is often prone to blockage during field harvesting operations, which is why it is very important to study the working load of its drive shaft. To obtain the true load of the drive shaft of the feeding and conveying device for combine harvester under typical field operating conditions, the domestic 12 kg/s wheeled combine harvester was taken as the test object and a field load test system was constructed based on the perception of strain torque sensor and speed sensor. Through the field load tests, the results showed that the maximum power consumption of the drive shaft was 4.06 kW under the harvesting operation conditions and the average power consumption was 1.56 kW. Based on the rainflow counting method, the two-dimensional extrapolation load spectrum of the key power input section of the drive shaft under typical operating conditions was compiled by using the matrix cyclic period extrapolation method, which can provide loading conditions for the fatigue life test of the drive shaft of the feeding and conveying device for combine harvester. This method will provide a basis for the power matching of the working device of the harvester and a reference for the anti-fatigue design of the transmission system of the combine harvester. Keywords: combine harvester; feeding and conveying device for combine harvester; load test system; rainflow counting method; matrix cyclic period extrapolation method DOI: 10.25165/j.ijabe.20261902.10258 Citation: Zhang F, Li X S, Huang S C, Guo Z Q, Yu Z W, He H W, et al. Field test and load spectrum compilation on the drive shaft of feeding and conveying device for combine harvester. Int J Agric & Biol Eng, 2026; 19(2): 152–157.